Education on Exclusive Breastfeeding to Breastfeeding Mothers in the Pustu Sugiharjo Dusun II Village Batang Kuis - Saragih, Astri Ulina; Ginting, Desideria Yosepha (JURNAL PENGMAS KESTRA (JPK), 2024)
Exclusive breastfeeding plays a crucial role in the health of mothers and infants. Providing exclusive breastfeeding for the first six months of an infant's life can reduce the risk of child mortality and protect mothers from various diseases, including breast cancer. Despite its clear benefits, the global rate of exclusive breastfeeding remains low, with less than 40% of infants receiving exclusive breast milk. Factors such as maternal health issues, breast pain, and social stigma around breastfeeding in public often act as barriers. Method this program was implemented through a series of educational activities, including lectures, discussions, and Q&A sessions, emphasizing the importance of breast milk for the health of both mothers and infants. The outreach was attended by 20 breastfeeding mothers and took place on Friday, November 15, 2024, lasting 1 hour and 45 minutes. The program aims to encourage more mothers to adopt healthy breastfeeding practices. With ongoing support and guidance, it is hoped that awareness of the benefits of exclusive breastfeeding will increase, positively impacting the health of mothers, infants, and families. The program also highlights the importance of collaboration among healthcare providers, the government, and the community to create an environment that supports exclusive breastfeeding. As a result of this activity, breastfeeding mothers gained information and education about the importance of exclusive breastfeeding and how to implement it during the first six months after birth, particularly in the Sugiharjo Dusun II, under the jurisdiction of Pustu Desa Sugiharjo Batang Kuis.